Inequalities in the burden of non-communicable diseases across European countries - Andrade, Carlos Alexandre Soares (2023)
Funding Information: This publication is based upon work from COST Action CA18218 (European Burden of Disease Network; www.burden-eu.net ), supported by COST (European Cooperation in Science and Technology; www.cost.eu ). Publisher Copyright: © 2023, The Author(s).